Penyuluhan Strategi Pemasaran Digital Agrowisata di Desa Tengklik Kecamatan Tawangmangu Kabupaten Karanganyar - Setiyani, Rahmawati; Purwanto, Eko; Rahmadhani, Istining (Pakis Journal Institute, 2025)
Tengklik Village is located in Tawangmangu District, Karanganyar Regency. Tengklik Village has a natural landscape in the form of highlands and cold temperatures so that it is suitable for rice fields, plantations and livestock. With this typology, Tengklik Village has the potential for community-based agrotourism. The partner in this community service activity is Tengklik Village. The methods used in this community service activity are (1) discussion of identifying problems faced by partner, (2) counseling on digital marketing strategies for Tengklik Village agrotourism, and (3) evaluation of the implementation of community service activity. Based on the results of the discussion on identifying problem faced by partner, namely the potential for Tengklik Village agrotourism is not been managed properly so that tourist visits are still low. The purpose of this community service activity is to conduct counseling on digital marketing strategies for Tengklik Village agrotourism. Digital marketing strategies for Tengklik Village agrotourism that can be applied include utilizing social media accounts, preparing content in the form of posters, photos, and videos related to agrotourism, and collaborating with influencers who can help promote agrotourism. The results of the evaluation of the community service activity showed that participants were enthusiastic in following each stage of the activity. The implementation of this community service activity is expected to provide new experiences for partner and increase insight that can support the progress of Tengklik Village and improve community welfare.